Management of Knee Ankylosis Using Ilizarov Device - Enemudo, Roy T. Efetoboh (Nigerian Journal of Orthopaedics and Trauma, 2018)
Knee ankylosis is a common complication of knee trauma and infection that poses a serious challenge to orthopaedic surgeons regularly in their practice. This study highlights the success of the use of Ilizarov device in the management of fibrous ankylosis of the knee. A 37‑year‑old nurse with a fibrous ankylosed knee that had a range of movement (ROM) of 0°–40° was successfully treated with Ilizarov device, indomethacin (analgesics) and physiotherapy. Her ROM of the affected right knee improved to 0°–140° and after a follow‑up period became 0°–90°. She was very happy with the outcome. There was no associated knee pains afterwards. Ilizarov device, together with adequate analgesia and physiotherapy, can successfully treat knee ankylosis.